Development of a bioenergetics and population dynamics coupled model: A case study of chub mackerel - Wang, Ziqin; Ito, Shin-ichi; Yabe, Itsuka; Guo, Chenying (Frontiers in Marine Science, 2023)
A bioenergetics and population dynamics coupled model that includes a full life cycle and size/growth-dependent mortality function was developed to better understand stock fluctuations. As an example, the model was applied to chub mackerel (Scomber japonicus) as it shows large stock fluctuations in the western North Pacific. The mortality dependency parameters for growth/size were adjusted to achieve realistic stock fluctuations in the model from 1998 to 2018. Two types of mortality functions were used in the model: one based on both size and growth, and the other based solely on size. An increasing trend of stock fluctuation of chub mackerel in the 2010s was reproduced in the simulation by contributions of several strong monthly cohorts that formed strong year classes using both types of mortality functions. The reproducibility of the stock fluctuation was not markedly different between the models with the two types of mortality functions, which indicates the importance of size-dependent mortality on the stock fluctuations of chub mackerel. The influence of sea surface temperature (SST) and chlorophyll-a was evaluated separately by using the climatological values for one of the forcings, and the model results revealed that the stock fluctuations of chub mackerel during 1998–2018 were mainly controlled by chlorophyll-a, whereas the increasing stock during 2010–2014 was strongly influenced by chlorophyll-a, and that after 2014 was influenced by SST. When integrated with different fishing pressures, the model showed that high fishing pressure hinders the recovery of chub mackerel stocks, highlighting the importance of effective fishery management.